'I felt a little bubbly in my tummy': eliciting pre‐schoolers' accounts of their health visit using a computer‐assisted interview method. (12th November 2015) - Bokström, P.; Fängström, K.; Calam, R.; Lucas, S.; Sarkadi, A.
Abstract: Background: In the health care services, children's rights to participate in all matters that concern them are considered important. However, in practice this can be challenging with young children. In My Shoes (IMS) is a computer‐assisted interview tool developed to help children talk about their experiences. The aim of the study was to evaluate the IMS' ability to elicit pre‐schoolers' subjective experiences and accurate accounts of a routine health visit as well as the children's engagement in the interview process. Methods: Interviews were conducted with 23 children aged 4–5 years, 2–4 weeks after their health visit. The interviews were transcribed verbatim and analysed using a method inspired by Content Analysis to evaluate IMS's ability to elicit accounts about subjective experiences. Accurate accounts were assessed by comparing the transcribed interviews with the filmed visits at the child health centre. The children's engagement was defined by the completion and length of the interviews, and the children's interaction with the software. Results: All children gave accounts about their subjective experiences, such as their emotional state during the visit, available toys or rewards they received. All children related to the correct event, they all named at least one person who was present and 87% correctly named at least one examination procedure. The majority of children (91%) completed the interview, which lasted 17–39 min (M = 24), and 96% interacted with the IMS software. Conclusions: IMS was feasible to help children describe their health care experiences, in both detail and depth. The children interacted with the software and maintained their interest for an extended period of time.